Primordial Black Hole Mergers as Probes of Dark Matter in the Galactic Center - Qianhang Ding; Minxi He; Volodymyr Takhistov (The Astrophysical Journal)
Primordial black holes (PBHs) from the early Universe that can contribute to dark matter (DM) abundance have been linked to gravitational-wave observations. Supermassive black holes at the centers of galaxies are expected to modify the distribution of DM in their vicinity and can result in highly concentrated DM spikes. We revisit PBH merger rates in the presence of DM spikes, tracking their history. We find novel peaked structure in the redshift evolution of PBH merger rates at low redshifts around z  ∼ 5. These effects are generic and are present for distinct PBH mass functions and spike profiles, and also can be linked to peaked structure in the redshift evolution of the star formation rate. Redshift evolution characteristics of PBH merger rates can be distinguished from astrophysical black hole contributions and observable with gravitational waves, enabling them to serve as probes of DM in galactic centers.